(untitled) (Universal International Scientific Journal, 2026)
This paper analyzes contemporary patterns of violence, including domestic violence and women’s psychological characteristics. Strict isolation and women’s individual characteristics have exacerbated existing problems of violence and created new forms, particularly against women. They have become even more vulnerable to partner abuse and other risk factors, while prevention and rehabilitation services lag behind the demands of the social environment and safety, making them less accessible. Women’s well-being as individuals directly impacts societal development.